Exploring Halal: Food And Beverages Industry Through Conceptual Lens - MAZUKI, NUR MARFAIZA (Journal of Halal Research, Policy, and Industry, 2025)
The concept of Halal products and food has gained global interest due to its recognition as an alternative standard for ensuring safety, hygiene, and quality assurance in consumables. Consequently, products or food manufactured by Halal principles are deemed acceptable not only to Muslims but also to non-Muslim consumers. This concept paper provides a comprehensive overview of the contemporary Halal food and beverages industry, beginning with the key trends shaping its landscape. It explores both conventional practices and Islamic principles within the food and beverages industry in Malaysia, emphasizing compliance from an Islamic perspective. The paper reviews past and current literature on the development of the Halal food and beverages industry, with a depth discussion on supervision by the regulatory bodies and the use of the Halal logo. Additionally, recommendations for enhancing the Halal food industry's growth and sustainability are highlighted. In conclusion, this paper serves as a foundation for further research and strategic initiatives aimed at advancing the Halal food and beverages industry in Malaysia.